Serum ferritin levels are associated with carotid atherosclerosis in Chinese postmenopausal women: the Shanghai Changfeng Study. Issue 7 (12th August 2015) - Ma, Hui; Lin, Huandong; Hu, Yu; Li, Xiaoming; He, Wanyuan; Jin, Xuejuan; Gao, Jian; Zhao, Naiqing; Song, Binbin; Pan, Boshen; Gao, Xin
Abstract : Postmenopausal women are at increased risk of CVD: the increased serum ferritin level may be involved in the pathogenesis. The aim of the present study is to investigate the relationship of ferritin and carotid atherosclerosis in postmenopausal women. A total of 1178 postmenopausal women (mean age, 60·8 years) were enrolled from the Changfeng Study. A standard interview, anthropometric measurements and laboratory analyses were performed for each participant. Bilateral CIMT (carotid intima–media thickness) were measured using ultrasonography, and the presence of carotid plaques was assessed. Serum ferritin was measured using electrochemiluminescence immunoassay. The results showed that serum ferritin was 181·9 (sd 65·8) ng/ml in the postmenopausal women. Multivariate, linear, stepwise regression analysis demonstrated that age (standardised β = 0·233, P < 0·001), alanine transaminase (standardised β = 0·194, P < 0·001), log homeostasis model assessment index for insulin resistance (standardised β = 0·181, P < 0·001), TAG (standardised β = 0·083, P = 0·003), Hb (standardised β = 0·080, P = 0·004) and PPG (2-h glucose levels following a 75-g oral glucose challenge) (standardised β = 0·079, P = 0·004) were independently associated with serum ferritin. Compared with the ferritin level of subjects in the first quartile, that in the fourth quartile had greater CIMT, and higher prevalence of carotid plaque. After adjusting for conventional CVD risk factors, Hb, leucocytes, log urine albumin:creatinine ratio and liver function, the ferritin level of postmenopausal women in the fourth quartile had a 1·587-fold increased risk of carotid plaques relative to those in the lowest quartile. In conclusion, these results suggest that serum ferritin is independently and positively associated with carotid atherosclerosis in postmenopausal women and that ferritin may be implicated in atherosclerosis.